The Development of Diagnostic Test with Testlet Model to Detect Difficult Learning Students in Temperature and Its Changes Materials - Safitri, Rizqi Kurni; Dewi, Novi Ratna (Unnes Science Education Journal, 2020)
The science learning process in junior high school is expected to lead to the achievement of learning objectives. Learners can experience difficulties in the learning process that must be detected to maximize learning outcomes. This Research & Development study aims to determine the characteristics of the testlet diagnostic model and the profile of students' learning difficulties on the material temperature and its changes. The research design using the 4D model reduced to 3D includes: define, design, and develop. The study was conducted at SMPN 1 Semarang with a total of 39 students. Data collection techniques through test techniques, questionnaires, interviews, and documentation. Data analysis techniques using descriptive-quantitative methods through the test of characteristics (validity, reliability, level of difficulty, distinguishing power), questionnaire analysis of teacher and student responses, and analysis of learning difficulties profiles. The results showed that the diagnostic test of the testlet model can be used to detect learners’ learning difficulties in the temperature and its changes material. The developed testlet test model has valid, reliable, relevant, representative, practical, discriminative, specific, and proportional characteristics. Profile of learning difficulties in the material temperature and its changes, namely, verbal ability, the highest and lowest of 64% and 31% in Competency Achievement Indicators 6 and 3; mastery of concepts, the highest and lowest of 68% and 31% in Competency Achievement Indicators 8 and 5; and the ability to count, the highest and lowest of 75% and 9% in Competency Achievement Indicators 5 and 1.